2013
DOI: 10.1159/000353297
|View full text |Cite
|
Sign up to set email alerts
|

Study of <b><i>VSX1</i></b> Mutations in Patients with Keratoconus in Southwest Iran Using PCR-Single-Strand Conformation Polymorphism/Heteroduplex Analysis and Sequencing Method

Abstract: Objective: Keratoconus (KC) is an eye disorder in which the cornea is swollen, thinned and deformed. Despite extensive studies, the pathophysiological processes and genetic etiology of KC are unknown. The disease incidence is approximately 1 in 2,000, and it is the most common cause of corneal transplantation in the USA. Many genes are involved in the disease, but evidence suggests a major role for VSX1 in the etiology of KC. This study aimed to determine the frequency of mutations in exons 2, 3 and 4 of the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…However, in the same study the SOD1 intronic 7-base deletion (c.169 + 50delTAAACAG) was over-represented among keratoconic patients compared to healthy controls [52]. R166W and H244R VSX1 variants might play critical role in the pathogenesis of keratokonic corneas, as suggested by SaeeRad et al [53].…”
Section: Other Genes Implicated In Keratoconus Pathogenesismentioning
confidence: 70%
See 1 more Smart Citation
“…However, in the same study the SOD1 intronic 7-base deletion (c.169 + 50delTAAACAG) was over-represented among keratoconic patients compared to healthy controls [52]. R166W and H244R VSX1 variants might play critical role in the pathogenesis of keratokonic corneas, as suggested by SaeeRad et al [53].…”
Section: Other Genes Implicated In Keratoconus Pathogenesismentioning
confidence: 70%
“…On the other hand Moschos et al reported no polymorphisms of VSX1 gene related to keratoconus [52]. However, in the same study the SOD1 intronic 7-base deletion (c.169 + 50delTAAACAG) was over-represented among keratoconic patients compared to healthy controls [52].…”
Section: Other Genes Implicated In Keratoconus Pathogenesismentioning
confidence: 82%
“…Recently, disease-causing VSX1 mutations were identified in New Zealand and Han Chinese cohorts 75,76 . However, studies conducted in South Indian, Iranian, and Greek populations found no significant association between VSX1 mutations and susceptibility to KC 7779 .…”
Section: Keratoconus (Kc)mentioning
confidence: 90%
“…Gly 239 ArgPathogenic a, b KeratoconusItalian[29]p. His 244 ArgUnknownKeratoconus+Caucasian, Iranian[16, 18, 34, 37]p. Ser 251 ThrUnknownKeratoconusIndian[22]p.…”
Section: Discussionmentioning
confidence: 99%